If the fourth term in a geometric sequence is –1 and the common ratio is –1, find the explicit formula of the sequence.

A)

an = (1) ⋅ (–1)n – 1 for n ≥ 1

B)

an = (– 1) ⋅ (1)n – 1 for n ≥ 1

C)

an = (–1) ⋅ (–1)n – 1 for n < 1

D)

an = (1) ⋅ (1)n – 1 for n ≥ 2

Respuesta :

caylus

Answer:

Hello,

Answer A

Step-by-step explanation:

[tex]a_4=-1\\q=-1\ common\ ratio\\\\a_4=a_1*q^3\ -1=a_1*(-1)^3 \Longrightarrow\ a_1=1\\\\\\\boxed{a_n=1*(-1)^{n-1}}\\\\\\Since \ all \ formula\ are\ so\ bad\ written,\ I\ suppose\ that\ the\ answer \ is \ A\\[/tex]

Answer:

 

an = (1) ⋅ (–1)n – 1 for n ≥ 1

Step-by-step explanation:

took the test and got it right

hope this helps